Hero Stone depicting the hero and his journey to the heavenly abode - Temples of India Project Team (Jio Institute, 2024)
Seen here is a small size hero stone, similar in dimensions to the adjacent hero stones. It is a rectangular stone slab without a triangular finial. The panel depicting the hero and his journey to the heavenly abode differs slightly from others. Here, there is no figure mounted on a horseback; instead, there is a supine human figure next to another figure standing with folded hands. The depiction likely indicates the hero’s death and his attainment of moksha (freedom from the eternal cycle of life, death, and rebirth). This unique portrayal is not found on any other hero stones fragment in the Suswani Mata Temple.